Perubahan Dokumen Hazard Identification Risk Assessment and Risk Control (HIRARC) di PT. Schneider Electric Indonesia - Maubere, Elizabeth Kartika; Panjaitan, Togar W.S. (Jurnal Titra, 2014)
PT. Schneider Electric Indonesia is one of the electrical manufacturer in Indonesia. The company has a HIRARC document which is based on OHSAS 18001:2007 standard. The last updated of HIRARC document was in 2013. The production proses activities have been changed in 2014 and required adjustment, including the changes of HIRARC document. This research was conducted to make HIRARC document fit with the actual conditions. After the identification of hazards, there is a change in the amount of activities that are at risk condition. HIRARA 2014 document showed 2 activities at high level of risk, 69 activities at moderate level of risk, and 436 activities at low level of risk at LV (Low Voltage) production line and FQC (Final Quality Control) LV production line.